2015 IEEE 12th International Symposium on Biomedical Imaging (ISBI) 2015
DOI: 10.1109/isbi.2015.7164058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an annular sleeve of high permittivity material on resonant modes and homogeneity of a birdcage coil

Abstract: Fig. 1 Simulation set-up. High pass head-sized birdcage with a dielectric (blue) sleeve (A, B) or brick (C) with dimensions 3.5 cm x 8.5 cm x 26 cm. ABSTRACTWe investigated how high permittivity materials affect the S-parameters and transmit efficiency of a head-sized birdcage coil. We also studied whether re-tuning and matching are necessary for improved performance. While adjusting the S-parameters is possible during coil development and for prototype coils, it is often unfeasible to re-tune and match commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In previous studies, dielectric pads with a relative permittivity of ∼300 have been shown to increase the transmit efficiency and reduce the specific absorption rate (SAR) in cardiac , abdominal , and cervical spine applications at 3T. In the current work, materials developed by the Penn State group with relative permittivity values more than three times greater than those used in previous body imaging studies are investigated. The effect of these materials on the transmit RF field, receive sensitivity, and overall diagnostic quality of the images has been analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, dielectric pads with a relative permittivity of ∼300 have been shown to increase the transmit efficiency and reduce the specific absorption rate (SAR) in cardiac , abdominal , and cervical spine applications at 3T. In the current work, materials developed by the Penn State group with relative permittivity values more than three times greater than those used in previous body imaging studies are investigated. The effect of these materials on the transmit RF field, receive sensitivity, and overall diagnostic quality of the images has been analyzed.…”
Section: Introductionmentioning
confidence: 99%